Effect of Lingnan Painless Apitherapy combined with McKenzie Therapy on Patients with Lumbar Disc Herniation - Hongbo WU; Xinghua CHEN; Ruike ZHANG; Qinglu LUO; Yongming CHENG (康复学报)
Objective:To observe the clinical efficacy of Lingnan painless apitherapy combined with McKenzie therapy on patients with lumbar disc herniation(LDH).Methods:A total of 80 patients with LDH who were treated in the department of rehabilitation medicine of the fifth affiliated hospital of Guangzhou medical university from February 2019 to June 2020 were randomly divided into the control group and the observation group according to the random number table method, with 40 cases in each group.The control group received magnetic thermal-vibration therapy and McKenzie therapy.The Japanese magnetic thermal-vibration therapy instrument(TM-3200)was used in the magnetic thermotherapy, the appropriate intensity(high, hot, warm and low temperature)was selected according to the patient's feeling and symptoms, 20 minutes each time, once a day, seven times a week, continuous treatment for two weeks.In addition, the patients with LDH received McKenzie therapy, which was assisted by the therapist or the patient actively completed the flowing training, such as prone position stretching, prone position stretching combined with compression, standing position lateral movement and so on.Each step rested for one minute, once every two days, continuous treatment for two weeks.The observation group received Lingnan painless apitherapy on the basis of treatment in the control group after half an hour's rest.Before treatment, the patients were given apitherapy tolerance test, performing apitherapy with one bee on each Zusanli acupoints on both sides.After apitherapy for 15 minutes, if there was no adverse reaction, the patients were given painless apitherapy with a quiet and comfortable environment, every other day.In this treatment, both sides of Huatuo Jiaji acupoints on the lumbar spinous processes were selected, and Huatuo Jiaji acupoints on both sides of the 5th lumbar spinous process were selected in the first treatment, one acupoint on the left and one on the right.After that, two acupoints were added each time, and each acupoint was treated by one bee.According to the order of Jiaji points on the 4th, 3rd, 2nd and 1st lumbar vertebrae, the number of bee needles increased to 10 bees.Before treatment and two weeks after treatment, visual analogue scales(VAS)was used to evaluate the pain degree, Oswestry disability index(ODI)was used to assess the lumbar spine dysfunction, and TCM syndrome score was used to evaluate the therapeutic effect, and the clinical efficacy was evaluated by the diagnosis and curative effect standards of TCM diseases.Results:Before treatment, there was no significant difference in the VAS score, ODI score and TCM syndrome score between the observation group and the control group(P>0.05).Compared with treatment before, the VAS score, ODI score and TCM syndrome score after treatment for two weeks of the two groups were significantly reduced, with a statistically significant difference(P<0.05).Compared with the control group, the VAS score and TCM syndrome score of the observation group were lower than those of the control group, with a statistically significant difference(P<0.05), but there was no considerable difference in ODI score between the two groups(P>0.05), and the clinical efficacy of the observation group(95%)was significantly higher than that of the control group(80%)(P<0.05).Conclusion:Lingnan painless apitherapy combined with McKenzie therapy can significantly improve the pain degree and lumbar spine dysfunction of patients with LDH, which have a good effect and it is worthy of clinical promotion.However, it's necessary to develop large-sample randomized controlled trials and follow-up, to provide more reliable basis for clinical treatment of LDH.